Diagnostic set-up and modelling for investigation of synergy between 3D edge physics and plasma-wall interactions on Wendelstein 7-X. (10th May 2017) - Liang, Y.; Neubauer, O.; König, R.; Krychowiak, M.; Schweer, B.; Denner, P.; Rack, M.; Reiter, D.; Feng, Y.; Krämer-Flecken, A.; Drews, P.; Hasenbeck, F.; et al.
Abstract: A group of edge diagnostics and modelling has been developed for investigation of synergy between 3D edge physics and plasma-wall interactions on Wendelstein 7-X (W7-X). Two endoscopes have been designed for visible and ultraviolet spectroscopy and tomography of the plasma edge, along with infrared thermography of the divertor tiles. 2D profiles of impurities (e.g. helium, carbon) will be measured by two endoscopes viewing the island divertor region in the plasma edge with a spatial resolution of  <2 mm. A multipurpose manipulator, which is used as the carrier either of the probe head for measuring the plasma edge profiles or of samples for plasma exposure studies, was installed at the outside mid-plane on W7-X in 2015. A poloidal correlation reflectometer has also been installed at W7-X. The system consists of an antenna array observing the propagation of turbulent phenomena in the mid-plane. The EMC3-EIRENE code package has been adapted for plasma edge transport in helium plasma at W7-X using a hybrid fluid–kinetic approach by enabling EMC3 to treat non-hydrogen isotopes and extending the usage of EIRENE features within EMC3-EIRENE.